Pengetahuan, sikap dan praktik ibu dalam pemberian makanan sehat keluarga di Kota Semarang - Shaluhiyah, Zahroh; Kusumawati, Aditya; Indraswari, Ratih; Widjanarko, Bagoes; Husodo, Besar Tirto (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Anemia prevalence among pregnant women in Central Java 2016 was 40.1% and 27.9% among fertile women aged 15-44 years. Anemia among pregnant mothers usually caused by ferrum defficiency due to low nutritional intakes during youth. The provision and processing of food at the family level that carried out mostly by mother were also the factors which related to nutrional problems at family level.Objectives: This study aims to identify mothers’ knowledge, attitudes, and practices in providing nutritional food for their family, pregnant women and children under five years old. Methods: An explanonatory research with cross-sectional survey has been conducted among mothersin Karanganyar Gunung and Karangayu Semarang. The mothers were selected using systematic random sampling with inclusion criteria were either pregnant or having children under five and willing to participate in this study. Of 200 mothers had participated in this survey. Data were collected by enumerator using structure questionnaires which have been validated before. Univariate, Chi-Square and logistic regression tests have been employed to analyze the data.Results: Nearly half of mothers have been categorized as poor practices in providing healthy food for their families (47%). More than half (56%) have good knowledge, but only 45.5% have positive attitudes towards providing healthy food. Mothers’ age (p = 0.048; OR = 0.547), education level (p = 0.042; OR = 0.580) and attitudes of providing healthy food (p = 0.001; OR= 3.138) were the influencing factors on providing healthy food. Conclusion: Mothers with positive attitudes have more likely to provide a healthy food for their families three times higher than those who have negative attitudes. Whilst, mothers who have aged ≥30 years were more likely to have protection (OR < 1) to provide healthy food than those who have aged <30 years. Likewise, mothers who have high education level were more likely to have protection to provide healthy food compare to those who have low education level.